The Writing Modalities of (In)terdiscourse: From Journalism to the Essay in In the Name of Identity by Amin Maalouf - Souames, Amira (El Omda in Linguistics and Discourse Analysis, 2023)
We will focus in this paper on the hybrid nature of Amin Maalouf’s writing. We will reflect on this hybrid aspect of Maaloufian writing. Through In the Name of Identity, we aim to demonstrate the relationships woven between journalistic discourse and literary discourse. This hybridity appears not only in the interweaving of various discursive genres (letter, poem, press article, etc.), but also in the incorporation of other discourses into literary discourse (autobiographical, religious, journalistic, etc.), thereby forming an interdiscourse that needs to be defined.